Goethe's Wilhelm Meister's Apprenticeship and philosophy - Eldridge, Sarah Vandegrift; Speight, Allen (New York : Oxford University Press, 2020)
"Goethe's Wilhelm Meisters Lehrjahre served as a touchstone for major philosophical and literary figures of his age (including, among many others, Schiller, Fichte, Hegel, Schlegel, Schleiermacher and Novalis). But it has received far less attention in both disciplines (especially in English-language scholarship) than either Goethe's Sorrows of Young Werther or Elective Affinities. This volume takes up the question of what Goethe's long and rather complicated novel is doing and how it engages with problems and themes of human life more generally, including issues of individuality, development, and authority; aesthetic formation and narrative (and human) contingency; gender, sexuality, and marriage; about power, institutions, and control"--
Includes bibliographical references (pages 265-268) and index.
Keywords: Goethe, Johann Wolfgang von, -- 1749-1832. -- Wilhelm Meisters Lehrjahre